Brain tumors. A bibliometric analysis of forty years by science mapping - Kuytu, Turgut (The European Research Journal, 2025)
Objective: Science mapping is a systematic approach to analyzing the intricate network of relationships in the scientific literature. Science mapping methodology investigates the networks of relationships among scientific articles, authors, journals, keywords, and research topics. This study aims to comprehend the literature in the field of brain tumors. Methods: Our study covers the period 1980-2022. Our study uses the Web of Science database for literature reviews and bibliometric analyses. The obtained data were filtered and classified. The 10,777 articles were analyzed in five sections. Some of sections are: structural analysis of the articles, analysis of countries, keyword analysis, thematic analysis, and the collaboration analysis. Results: The articles have been published in 1761 journals. The average citation per article is 38.22. The highest h and g-index values belong to Cancer Research. For thematic analysis, the period from 1980 to 2022 has been analyzed. During 2021-2022, ’Deep Learning’ and ’Brain Tumors’ formed the motor themes. The authors’ collaboration network is analyzed. Kun LE is the author with the most collaborations. Conclusions: Upon examining thematic maps from all periods, it is assessed that the likely topics and scopes of future research on brain tumors will be biomarkers, personalized treatments, artificial intelligence, immunotherapy, and pediatric brain tumors.